The Effectiveness of Role-Playing Methods for Early Childhood Emotional Social Development and Independence - Meilina, Henny; Sugiyo, Sugiyo; Astuti, Budi (Journal of Primary Education, 2021)
This research is focusing on the development of early childhood character, especially social emotional and child independence. This study aims to analyze the effectiveness of role-playing learning for the development of emotional social attitudes and independence of early childhood. The research is an experimental method with a quasi-experimental type of research and pretest-posttest design. The research population is all Kindergarten students in the target area 5, Godong District, Central Java. The research sample are 22 children. Sampling used a suitability random draw technique. The data analysis technique used the statistical calculation of the Mann-Whitney test. The results of the study indicate that the themed role-play learning in collaboration to develop children's social emotional character obtained a mean value of 42.07 from the maximum score of 50. The development of self-reliance character, learning to play a role obtained a mean value of 33.82. This shows that role playing learning is more effective for developing social emotional characters compared to the development of students' independent character with a mean difference of 8.25.